PENERAPAN MODEL PEMBELAJARAN SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATIC (STEM) UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMK PERTANIAN PEMBANGUNAN NEGERI LEMBANG - Shaila Rismayaingrum, - (2020)
STEM is a learning approach that connects four fields, namely science, technology, engineering, and mathematics into a holistic whole. This study aims to determine how much improvement in student learning outcomes by applying the Science, Technology, Engineering, and Mathematic (STEM) Learning Model on the basic competencies of processing legumes at SMK PPN Lembang. The research method used was classroom action research (PTK). Research data in the form of learning implementation and cognitive learning outcomes obtained from pre-test and post-test, affective learning outcomes obtained from attitude assessment and psychomotor learning outcomes obtained from practicum assessment sheets. The implementation of learning in the third cycle is carried out 100% in the very good category. The results of the analysis using the N-gain test on student cognitive learning outcomes data from cycle I, cycle II and cycle III showed an increase. The increase in learning outcomes can be seen from the N-Gain value in cycle I of 0.37, then increased to 0.40 in cycle II and 0.51 in cycle III. The average achievement of cognitive learning outcomes from cycle I was 40%, then increased to 55% in cycle II and 65% in cycle III. The average achievement of affective learning outcomes from cycle I was 55%, then increased to 85% in cycle II and 100% in cycle III. The average achievement of psychomotric learning outcomes from the cycle in the second cycle. The results of the observation of the learning process and student activities were carried out according to the STEM learning stage. Thus it can be concluded that the Learning Model Science, Technology, Engineering, And Mathematic (STEM) can improve student learning outcomes.